ANXIETY OF HEMODIALYSIS PATIENT WITH ACCESS ARTERIOVENOUS FISTULA (AV-SHUNT): A QUALITATIVE STUDY - Siti Nafisah; Meira Irawati; Wahyu Hidayati (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Cannulation is an intervention that inserts a needle through the skin into a blood vessel. Av-shunt is the most recommended access for use in the hemodialysis therapy process. Psychosocial problems, especially feelings of anxiety and fear can be felt by patients due to AV-shunt. Anxiety is a scientific attitude experienced by each individual as a form of response in dealing with problems or threats Vascular access complications may threaten lives and reduce treatment satisfaction and life quality. Objectives: This study aimed to describe hemodialysis patient anxiety with arteriovenous fistula (AV-shunt) access. Methods: A descriptive qualitative study using the in-depth interview method with phenomenology approach. The study was carried out with four informants undergoing hemodialysis in RSUD dr. Haryoto Lumajang. Samples were taken using purposive sampling. Participant statements were recorded using a voice recorded, transcribed, coded, interpreted, and categorized to create a theme. Results: The study results produced three themes: (1) Emotional feeling perceived associated with AV-shunt experience: Anxiety, fear, and helplessness, (2) Physical and physical activity changes: Dark skin, dry skin, limp body, and fatigue, and (3) Patient knowledge regarding av-shunt, i.e., AV-shunt access and based on information sources. Conclusion: Patients with arteriovenous fistula (AV-shunt) access had anxieties caused by cannulation initial pain, fear, and sense of uselessness.